Śrīvidyāntargatā caturthī Bhuvaneśvarī mahāvidyā: 'Jñāna'-'Saparyā' khaṇḍātmikā - Prahlāda Giri, Gosvāmĩ ca. 20./21.Jh. (Bitthaldas Sanskrit series, 2017)
Hindu tantric text dealing with the rituals, tantra and mantra of Bhuvaneśvarī, 4th form of Śakti, Hindu diety